Evaluation of Complementary Cupping Therapy in the Management of Hypertension and Triglyceride Levels in Coastal Fishermen Communities - lilin, lilin rosyanti (Public Health of Indonesia, 2024)
Background: Fishermen are community groups requiring special attention. The characteristics of a stressful job, unhealthy diet, and environmental and weather conditions are risk factors for hypertension and increased triglycerides. Wet cupping therapy is expected to improve imbalance in triglyceride levels, blood pressure, and pulse rate in fishermen living in coastal areas. Methods: Sixty people from fishing communities participated in this study through random sampling by creating a serial number list. The hypertensive group (n= 30) received cupping therapy combined with Al-Quran therapy, whereas the normotensive group (n= 30) only received cupping therapy. Blood pressure, pulse, and triglyceride levels were measured in both groups before and one week after cupping therapy. Results: In the hypertension group who were administered cupping therapy combined with Al-Quran therapy, there were changes in blood pressure, mean systolic blood pressure value (from 155.4 ± 21.8 to 141.3 ± 19.9), diastolic blood pressure (from 92.9 ± 10.6 to 85.3 ± 11.3), and triglyceride levels (from 259.4 ± 154.6 to 173 ± 74.5), which showed a statistically significant decrease in P value <0.05, while the normotensive group was statistically significant, but there was an increase within normal limits in systolic blood pressure and diastolic blood pressure, as well as a decrease in triglyceride levels. Conclusion: The results of this study showed that wet cupping combined with Al-Quran therapy is a promising complementary therapy for controlling blood pressure and triglyceride levels in hypertensive patients. Therefore, it could be an alternative therapy for fishing communities in coastal areas.